The European Union and Turkish accession : human rights and the Kurds - Yildiz, Kerim; Müller, Mark (Pluto Press, 2008)
The EU accession process will shape Turkey's future and, in particular, its potential to become a pluralist, democratic state with respect for international human rights. In this timely survey, Kerim Yildiz and Mark Muller explain and analyze the process of accession focusing primarily on these associated human rights obligations and the extent of their implementation in Turkey. "The European Union and Turkish Accession" addresses the variety of groups in Turkey who are affected by these negotiations and details the background of the Kurdish people - the largest minority group in Turkey - and their relationship to the Turkish republic. This book is essential for students studying EU enlargement, particularly the human rights issues around the Turkish Accession, and those interested in the ongoing struggle of the Kurds. -- Publisher description